26th IUFRO World Congress - Forests and Society Towards 2050 Sweden, Stockholm | 23-29 June 2024 - Trébuchon, Jean-François (BOIS & FORETS DES TROPIQUES, 2023)
Demands of forest ecosystem services grow up due to the climate crisis and the need to reinforce the bioeconomy sector, the social services of healthy forests as established by the UN sustainable development goals, and forest resilience to disturbances and anthropogenic pressures. By 2050, drastic changes are expected in population growth, climate change, biodiversity loss, globalization and a growing world economy, putting tremendous pressure on forests and the societies who depend on them. 2050 is a landmark year to achieve the vision of Living in Harmony with Nature of the Convention on Biological Diversity as well as the target of net zero emissions. With a focus on forest contribution to the UN 2030 Agenda and its sustainable development goals (SDG), the IUFRO World Congress in Stockholm 2024 will help streamline forest research agendas, furthering dialogues and cross-sector cooperation, and promote the multi-functionality of forests and their services.